A LONG ROAD TO JUSTICE : STORIES FROM THE FRONTLINES IN ASIA - Friedman, Sylvia Yu (Singapore : PENGUIN BOOKS, An imprint of Penguin Random House, 2021)
A constant stream of impoverished women and girls have been, and are being, enslaved and abused in the Asia Pacific region. Slavery is not a historical issue - it's happening today. History is repeating itself. Through Sylvia Yu Friedman's work in journalism, counter-trafficking and philanthropy, she has had rare and incredible access to victims of sex trafficking and modern slavery in China, Thailand, Cambodia, North Korea, South Korea, Myanmar and Indonesia. Amid this terrible human suffering, she has seen frontline workers carrying a great light that has overcome the darkness in some of the most frightening places on Earth. This memoir describes her personal journey in the fight against slavery through supporting philanthropic initiatives and raising awareness through writing articles and producing films. She shares her personal setbacks, and how her awakening to the plight of the victims of Imperial Japanese sex slavery during World War II helped her come to terms with her identity issues over her Korean heritage. She writes about the lessons - the good, the bad, and the ugly - and the people and events that have shaped her along the way.
Keywords: Friedman, Sylvia Yu; Human trafficking -- Asia; Child trafficking -- Asia; Slave labor -- Asia; Poor -- Employment -- Asia; Slavery -- Asia